Imprinted DNA methylation reconstituted at a non-imprinted locus - Taylor, David H. (Epigenetics Chromatin, 2016)
BACKGROUND: In mammals, tight regulation of cytosine methylation is required for embryonic development and cellular differentiation. The trans-acting DNA methyltransferases that catalyze this modification have been identified and characterized; however, these proteins lack sequence specificity, leaving the mechanism of targeting unknown. A cis-acting regulator within the Rasgrf1 imprinting control region (ICR) is necessary for establishment and maintenance of local imprinted methylation. Here, we investigate whether 3-kb of sequence from the Rasgrf1 ICR is sufficient to direct appropriate imprinted methylation and target gene expression patterns when ectopically inserted at the Wnt1 locus. RESULTS: The Rasgrf1 ICR at Wnt1 lacked somatic methylation when maternally transmitted and was fully methylated upon paternal transmission, consistent with its behavior at the Rasgrf1 locus. It was unmethylated in the female germline and was enriched for methylation in the male germline, though not to the levels seen at the endogenous Rasgrf1 allele. Wnt1 expression was not imprinted by the ectopic ICR, likely due to additional sequences being required for this function. CONCLUSIONS: We have identified sequences that are sufficient for partial establishment and full maintenance of the imprinted DNA methylation patterns. Because full somatic methylation can occur without full gametic methylation, we infer that somatic methylation of the Rasgrf1 ICR is not simply a consequence of maintained gametic methylation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13072-016-0094-0) contains supplementary material, which is available to authorized users.